Isolation and Antimicrobial Susceptibility Profile of Escherichia coli from Urine Samples of Pregnant Women Attending Antenatal Clinics in Selected Hospitals within Kaduna Metroplolis, Nigeria - Tijjani, R. J.,; Yahaya, O.; Inabo, H. I. (UMYU Journal of Microbiology Research)
Urinary tract infections (UTIs) remains the most common infections diagnosed among in and  out patients as well as hospitalized patients. A total of 400 urine samples were collected from pregnant women attending selected hospitals within Kaduna Metropolis, Nigeria and analyzed for E. coli associated urinary tract infection. E. coli was isolated using Eosin methylene blue agar, and preserved on Nutrient agar slant. The isolates were identified based on cultural characteristics, conventional biochemical test and microgen kit identification. The antimicrobial susceptibility pattern of the isolate was determined using the Kirby-Bauer disc diffusion method. Out of the 400 samples collected, 85 (21.3%) were positive for Escherichia coli. In relation to the age-group, pregnant women within the age group 26-30 years had the highest prevalence of infection (28.3%), followed by pregnant women within the age of 31-35 years (18.9%), pregnant women with the least prevalence are within the age 15-20 years (18.3%). Pregnant women who were housewives had the highest prevalence of E. coli infection. Women in their 2nd and 3rd trimesters were found to have a higher prevalence of Escherichia coli infection; 21.7% and 23.0% respectively. This shows that high parity is one of the possible factors affecting the prevalence of urinary tract infection among pregnant women. Escherichia coli isolates showed highest susceptibility to Gentamicin (72.9%), Amoxycillin (70.5%) and Streptomycin (70.5%). However, the isolates showed higher resistance to Perfloxacin (49.4%), Chloramphenicol (38.8%), and Ciprofloxacin (36.5%).